Functional vertebrate group diversity differentially impacts vector‐borne pathogen transmission and genetic diversity - Marie Lilly; Arielle Crews; Alexandra Lawrence; Jordan Salomon; Samantha Sambado; Liliana Cerna; Kacie Ring; Ceili Peng; Grace Shaw; Shannon Summers; Andrea Swei (Ecosphere, 2025)
Abstract Anthropogenic land use change has led to considerable biodiversity loss, affecting ecosystem functions with unresolved consequences for zoonotic disease transmission. Functional diversity is understudied but potentially important for understanding the role of biodiversity because many zoonotic disease systems are maintained by species with different roles in disease transmission. Here, we explore how functional groups and pathogen genetic diversity influence transmission and human disease risk within the Lyme disease system. Our field and molecular ecology study examined ticks and vertebrates across a fragmented landscape and evaluated several metrics of disease risk. For predicting vector and infected vector density, rodent host richness had a positive effect and was most important, but vector infection prevalence was best predicted by rodent and predator richness together, reflecting how indirect effects may alter tick–host interactions and disease risk. These results indicate that examining species richness generally may obscure important interactions driven by richness within functional groups. Pathogen genotype richness was best predicted by overall vertebrate richness, providing support for the multiple niche polymorphism hypothesis. Our study offers an important perspective on the relationship between biodiversity and disease risk, suggesting that richness within functional groups may offer more nuanced insight into pathogen transmission dynamics than overall biodiversity.